Odontogenic Necrotizing Fasciitis in the Neck and Thoracic Region: A Case Report - Tangkilisan, Adrian; Sukanto, Wega; Tamburian, Christa; Satriadi, Wayan (Universitas Sam Ratulangi, 2025)
Abstract: Mediastinitis and necrotizing fasciitis are the most threatening complications of odontogenic infection that are not appropriately treated. We reported a 32-year-old woman with odontogenic necrotizing fasciitis in the neck and thoracic region due to second and third lower molar infection that started and progressed in ten weeks. This disease course was initiated by a small abscess in the submandibular region that spread to the neck and right chest. This condition did not progress into mediastinitis which had a poorer prognosis. Early rupture of the abscess may prevent the extent of the infection into the mediastinum. The patient’s condition improved after consuming antibiotic, analgesic, and debridement performed on her. The case management was consistent with the literature. The patient only came for first follow-up and then loss-to-follow-up. Therefore, skin flap surgery cannot be conducted. Keywords: necrotizing fasciitis; odontogenic source; neck; thoracic region